Organization of delta-crystallin genes in the chicken. - Yasuda, K (1982)
Double-stranded DNA was synthesized from delta-crystallin mRNA prepared from lens fibers of 15-day-old chick embryos and cloned at the Pst I site of the plasmid pBR322. Using the cloned cDNA and single-stranded cDNA as hybridization probes, a number of genomic DNA fragments containing delta-crystallin gene sequences have been cloned from the partial and complete EcoRI digests of chick brain DNA. One of the clones from the partial digests contains a DNA fragment that consists of four EcoRI fragments of 7.6 kb, 4.0 kb, 2.6 kb, and 0.8 kb. The gene sequences reside in the (5')7.6 kb - 0.8 kb - 4.0 kb (3') fragments. Electron microscopy has provided evidence that the cloned DNA fragment includes the entire gene sequences complementary to delta-crystallin mRNA except for the 3' terminal poly(A) tail, and that the delta-crystallin gene is interrupted by at least 13 intervening sequences. Another clone contains a genomic fragment that consists of two EcoRI fragments of 3.0 kb and 11 kb. The DNA fragment in the latter clone represents a different delta-crystallin gene, as judged by restriction endonuclease mapping and by electron microscopy.